Leadership in Surgery - Maykel, Justin A. (Clinics in Colon and Rectal Surgery, 2013)
Many opportunities exist for surgeons to be leaders in healthcare. Leadership training should begin in medical school and continue throughout residency training and in clinical practice. Most leadership skills can be developed and refined through a variety of training programs. Formal programs that result in degrees can provide surgeons with special insight, experience, and skill sets. Leadership skills are used in everyday practice and are particularly valuable when shifting roles or taking on new positions, whether at your home institution or within national organizations. Ultimately, physician leaders are responsible for leading healthcare and will directly impact the quality of care delivered to our patients.
Keywords: leadership; management; physician leader